A Functional High-Load Exercise Intervention for the Patellar Tendon Reduces Tendon Pain Prevalence During a Competitive Season in Adolescent Handball Players - Mersmann, Falk; Laube, Gunnar; Marzilger, Robert; Bohm, Sebastian; Schroll, Arno; Arampatzis, Adamantios (Frontiers in Physiology, 2021)
Imbalances of muscle strength and tendon stiffness may increase the risk for patellar tendinopathy in growing athletes. The present study investigated if a functional high-load exercise intervention, designed to facilitate tendon adaptation and reduce muscle-tendon imbalances, may prevent patellar tendon pain in adolescent male handball players (12-14 years). Tendon pain prevalence (using VISA-P scores), knee extensor strength, vastus lateralis (VL) architecture and patellar tendon mechanical properties were measured at four measurement time points (M1-M4) over a season. The control group (CON; n=18; age 13.1±0.7 yrs, height 170±8 cm, mass 58±10 kg) followed the usual strength training plan, including muscular endurance and explosive strength components. In the experimental group (EXP; n=16; 13.1±0.6 yrs, 169±11 cm, 58±16 kg), two sessions per week with functional high-load exercises for the patellar tendon were integrated in the strength training schedule, aiming to provide repetitive high intensity loading of at least 3 s loading duration per repetition. While in the control group 30% of the athletes reported a clinically significant aggravation of symptoms, all players in the experimental group remained or became pain-free at M2 until the end of the season. There was a similar increase of strength (normalized to body mass; CON: 3.1%, d = 0.22; EXP: 6.8%, d = 0.47; p=0.04) and VL thickness (CON: 4.8%, d = 0.28; EXP: 5.7%, d = 0.32; p<0.001) in both groups, but no significant changes of tendon stiffness or tendon strain. Further, both groups demonstrated similar fluctuations of tendon strain over time. We conclude that functional high-load exercises can reduce the prevalence of patellar tendon pain in adolescent athletes also without a reduction of tendon strain.